Application of remote sensing to understanding fire regimes and biomass burning emissions of the tropical Andes - Oliveras, I; Anderson, L; Malhi, Y (AGU Publications, 2014)
In the tropical Andes, there have been very few systematic studies aimed at understanding the biomass burning dynamics in the area. This paper seeks to advance on our understanding of burning regimes in this region, with the first detailed and comprehensive assessment of fire occurrence and the derived gross biomass burning emissions of an area of the Peruvian tropical Andes. We selected an area of 2.8 million hectares at altitudes over 2000 m. We analyzed fire occurrence over a 12 year period with three types of satellite data. Fire dynamics showed a large intra-annual and interannual variability, with most fires occurring May–October (the period coinciding with the dry season). Total area burned decreased with increasing rainfall until a given rainfall threshold beyond which no relationship was found. The estimated fire return interval (FRI) for the area is 37 years for grasslands, which is within the range reported for grasslands, and 65 years for forests, which is remarkably shorter than other reported FRI in tropical moist forests. The greatest contribution (60–70%, depending on the data source) to biomass burning emissions came from burned montane cloud forests (4.5 million Mg CO2 over the study period), despite accounting for only 7.4–10%of the total burned area. Gross aboveground biomass emissions (7.55 ± 2.14 Tg CO2; 0.43 ± 0.04 Tg CO; 24,012 ± 2685Mg CH4 for the study area) were larger than previously reported for the tropical Andes.